Training-Specific Neural Plasticity in Spinal Reflexes after Incomplete Spinal Cord Injury. (20th September 2016) - Khan, Atif S.; Patrick, Susan K.; Roy, Francois D.; Gorassini, Monica A.; Yang, Jaynie F.
Abstract : The neural plasticity of spinal reflexes after two contrasting forms of walking training was determined in individuals with chronic, motor-incomplete spinal cord injury (SCI). Endurance Training involved treadmill walking for as long as possible, and Precision Training involved walking precisely over obstacles and onto targets overground. Twenty participants started either Endurance or Precision Training for 2 months and then crossed over after a 2-month rest period to the other form of training for 2 months. Measures were taken before and after each phase of training and rest. The cutaneomuscular reflex (CMR) during walking was evoked in the soleus (SOL) and tibialis anterior muscles by stimulating the posterior tibial nerve at the ankle. Clonus was estimated from the EMG power in the SOL during unperturbed walking. The inhibitory component of the SOL CMR was enhanced after Endurance but not Precision Training. Clonus did not change after either form of training. Participants with lower reflex excitability tended to be better walkers (i.e., faster walking speeds) prior to training, and the reduction in clonus was significantly correlated with the improvement in walking speed and distance. Thus, reflex excitability responded in a training-specific way, with the reduction in reflex excitability related to improvements in walking function. Trial registration number is NCT01765153 .